ALKBH1 activity in vitro and human cell lines by isotope dilution mass spectrometry - Bennett Henzeler; Olga Hofmeister; Ken Kögel; Yuyang Qi; Felix Hagelskamp; Matthias Heiß; Florian Schelter; Felix Xu; Lena J. Daumann; Thomas Carell; Stefanie Kaiser; Sabine Schneider (PLoS ONE, 2026)
AlkB homolog 1 (ALKBH1) is a member of the AlkB family of Fe(II) and α-ketoglutarate (α-KG)-dependent dioxygenases, known for its enzymatic activity on various nucleic acid substrates. Its reported targets include N1-methyladenosine (m 1 A), N6-methyladenosine (m 6 A), N3-methylcytidine (m 3 C), and 5-methylcytosine (m 5 C) in RNA, as well as N6-methyladenine (N 6 -mA, 6mA) in DNA and the histone protein H2A. Moreover, dysregulation or dysfunction of ALKBH1 has been implicated in a broad spectrum of human diseases. In order to shed further light on the substrate scope and role of ALKBH1, we used quantitative mass spectrometry to assess its activity in vitro and in human cell lines. To study ALKBH1 activity on defined substrates in vitro , we enzymatically generated tRNAs specifically carrying the m 3 C32 (tRNA-Thr UGU and tRNA-Ser UCN ) and i 6 A37 (tRNA-Ser UCN ) modifications. Here we show that ALKBH1 reduces m 3 C, m 1 A and m 5 C in vitro in total extracts of tRNAs, but has no impact on rRNA modifications in human cell lines. However, upon overexpression or siRNA-mediated knock-down of ALKBH1 in human cell lines no impact on the modification of total tRNA extracts or specifically enriched RNAs could be observed. In addition, varying the glucose and fetal bovine serum (FBS) concentration in the growth medium of HEK293T cells, in combination with ALKBH1 siRNA-mediated knock-down, also shows no impact on tRNA methylation. Based on our data, we conclude that in human cells lines grown under optimal conditions ALKBH1 does not play an important role in the demethylation of tRNAs.